Imprecise system reliability and component importance based on survival signature. (June 2016) - Feng, Geng; Patelli, Edoardo; Beer, Michael; Coolen, Frank P.A.
Abstract: The concept of the survival signature has recently attracted increasing attention for performing reliability analysis on systems with multiple types of components. It opens a new pathway for a structured approach with high computational efficiency based on a complete probabilistic description of the system. In practical applications, however, some of the parameters of the system might not be defined completely due to limited data, which implies the need to take imprecisions of component specifications into account. This paper presents a methodology to include explicitly the imprecision, which leads to upper and lower bounds of the survival function of the system. In addition, the approach introduces novel and efficient component importance measures. By implementing relative importance index of each component without or with imprecision, the most critical component in the system can be identified depending on the service time of the system. Simulation method based on survival signature is introduced to deal with imprecision within components, which is precise and efficient. Numerical example is presented to show the applicability of the approach for systems. Abstract : Highlights: Survival signature is a novel way for system reliability and component importance High computational efficiency based on a complete description of system. Include explicitly the imprecision, which leads to bounds of the survival function. A novel relative importance index is proposed as importance measure. Allows to identify critical components depending on the service time of the system.